Efficacy of Bedaquiline, Alone or in Combination with Imipenem, against Mycobacterium abscessus in C3HeB/FeJ Mice - Le Moigne, Vincent (Antimicrob Agents Chemother, 2020)
Mycobacterium abscessus lung infections remain difficult to treat. Recent studies have recognized the power of new combinations of antibiotics, such as bedaquiline and imipenem, although in vitro data have questioned this combination. We report that the efficacy of bedaquiline-imipenem combination treatment relies essentially on the activity of bedaquiline in a C3HeB/FeJ mice model of infection with a rough variant of M. abscessus. The addition of imipenem contributed to clearing the infection in the spleen.